Opportunities for publication in open access pediatric journals in Latin America - Quispe-Juli, Cender U. (2023)
Objective: To explore the available options of Latin American pediatric journals in which open access articles can be published. Methodology: A descriptive observational study of Scopus-indexed journals was conducted for the year 2023. The country of the publisher, open access publishing option, management of proprietary copyright, license for sharing, languages of publication, and associated publication costs were examined. In addition, their positioning was evaluated according to the Scimago Journal Rank quartile and H-index. Results: The journals are concentrated in five countries, with the majority in Brazil (4/10) and Mexico (3/10). 90% (9/10) of the journals had open access editorial policies, of which 66.6% (6/9) were diamond open access. Only one of the journals allowed authors to retain proprietary copyright, but 80% (8/10) used the Creative Commons license. 40% (4/10) of the journals published articles exclusively in English, while only 20% (2/10) published an article in two languages simultaneously. Three journals charged article processing fees. Half of the journals were positioned in the third quartile of Scimago Journal Rank, and the median H-index was 12.5 (IQR: 7–21). Conclusion: The majority of pediatric journals in Latin America are open access, without associated publication costs, although there is some inequality in the geographic and linguistic distribution of publications. Journals should improve their visibility and positioning to be more attractive to readers and researchers.